Peningkatan Literasi Keuangan Desa: Peran Akademisi dalam Edukasi Teknologi Finansial dan Investasi - Hansen, Hansen; Mufrihah, Mazayatul; Hendri, Fransiskus Deny; Prangestu, Yoga; Ericko, Ericko (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
The low financial literacy in Penyeladi Village, Kapuas District, Sanggau Regency, has become a major barrier to effective financial management, especially in utilizing modern financial technology (fintech) and understanding investments. Most of the population, who work as farmers and small business owners, have not fully utilized financial technology, resulting in inefficient financial management and increased vulnerability to digital fraud. This community service program aims to enhance the understanding of financial management and investments through education and training tailored to local needs. The methods used include financial technology socialization, a workshop on creating Shopee Pay accounts, and investment management education for elementary school students and their parents. The results show an improvement in participants' knowledge in separating personal and business finances, as well as the ability to use fintech applications effectively and safely. This initiative is expected to have a positive impact on the community's economic stability, reduce fraud risks, and increase participation in the digital economy, supporting the village's future economic growth.